Coseismic Debris Remains in the Orogen Despite a Decade of Enhanced Landsliding. Issue 19 (7th October 2021) - Dai, Lanxin; Scaringi, Gianvito; Fan, Xuanmei; Yunus, Ali P.; Liu‐Zeng, Jing; Xu, Qiang; Huang, Runqiu
Abstract: Major earthquakes in steep orogens can trigger extensive landsliding. Most of the landslide bodies come to rest high on the slopes, but subsequent rainfalls can easily remobilize them. Sharp peaks in landslide rates are systematically observed after major earthquakes, followed by rapid decays to background levels in just several years. Yet, the migration of coseismic debris into tributary channels and rivers remains poorly understood. We collected 12 years of observations of the 2008 Wenchuan earthquake's epicentral region in China and evaluated that debris flows and fluvial transport could only evacuate a small portion of coseismic debris, while over 70% of it had stabilized on the hillslopes. Coseismic debris may remain in the orogen for a long time, but estimates based on initial landslide abundance and sediment export are hampered by uncertainties in the debris fate throughout the earthquake cycle. Plain Language Summary: Strong earthquakes leave a trail of destruction that lasts much longer than the dramatic minutes of strong ground motion. Earthquakes shake the mountains, causing extensive landsliding that delivers huge amounts of debris along the slopes and in drainage channels. This debris is loose and unconsolidated, prone to generating subsequent landslides and debris flows. We have monitored the epicentral area of the magnitude 7.9 Wenchuan Earthquake (2008, China) for 12 years to study the evolution of landslide activity in space, time, and characteristics, and track the fate of the debris from the slopes into channels and rivers. We found that the landslide rates have decreased rapidly. After 10 years, they were already comparable to the pre‐earthquake levels. Most of the debris remained on the slopes, though: it stabilized and never moved again. At current rates, the removal of the earthquake‐generated debris from the landscape through landsliding may take a long time. Key Points: Despite large amounts of erodible coseismic debris, post‐seismic landslide rates decayed to pre‐earthquake levels in less than a decade Only a small proportion of debris has left the orogen so far: over 70% of it has stabilized in place, along the hillslopes With erosion proceeding at this pace, a residence time of several centuries for the debris can be expected